Peran Psychological Capital dan Academic Resilience sebagai Prediktor Kesehatan Mental - Vera Sriwahyuningsih; Mufadhal Barseli (Jurnal Pendidikan Sosial Dan Konseling, 2026)
Mental health among university students is an important aspect in supporting academic achievement and optimal individual development. Various academic demands and life transitions during emerging adulthood may increase students’ vulnerability to psychological problems. Therefore, understanding positive psychological factors that support students’ mental health is essential, particularly Psychological Capital and Academic Resilience. This study aimed to examine the relationship between Psychological Capital, Academic Resilience, and Mental Health among students at Universitas Putra Indonesia YPTK Padang. This research employed a quantitative approach with a correlational design. The participants were 80 university students selected based on the research criteria. Data were collected using Psychological Capital, Academic Resilience, and Mental Health instruments. Data analysis was performed using Pearson Product Moment correlation to determine the direction and strength of relationships among variables. The results showed that Psychological Capital had a strong positive relationship with Mental Health with a correlation coefficient of r = 0.704. Academic Resilience also demonstrated a strong positive relationship with Mental Health with a correlation coefficient of r = 0.637. Furthermore, Psychological Capital was positively and strongly correlated with Academic Resilience with a correlation coefficient of r = 0.621. These findings indicate that higher levels of Psychological Capital and Academic Resilience are associated with better mental health among university students. The results provide implications for guidance and counseling services in higher education to develop promotive and preventive programs aimed at strengthening students’ positive psychological resources.